Laparotomy-Induced Peripheral Inflammation Activates NR2B Receptors on the Brain Mast Cells and Results in Neuroinflammation in a Vagus Nerve-Dependent Manner - Yang, Jing; Dong, Hong-Quan; Liu, Yan-Hu; Ji, Mu-Huo; Zhang, Xun; Dai, Hong-Yu; Sun, Zhao-Chu; Liu, Lu; Zhou, Jian; Sha, Huan-Huan; Qian, Yan-Ning; Li, Qing-Guo; et al. (Frontiers in Cellular Neuroscience, 2022)
Background: The pathophysiological mechanisms underlying postoperative cognitive dysfunction (POCD) remain unclear over the years. Neuroinflammation caused by surgery has been recognized as an important element in the development of POCD. Many studies also suggest that the vagus nerve plays an important role in transmitting peripheral injury signals to the central nervous system (CNS) and the resultant neuroinflammation. Previously, we have demonstrated that brain mast cells (BMCs), as the “first responders”, play a vital role in neuroinflammation and POCD. However, how the vagus nerve communicates with BMCs in POCD has not yet been clarified. Methods: In the current study, we highlighted the role of the vagus nerve as a conduction highway in surgery-induced neuroinflammation for the first time. In our model, we tested if mice underwent unilateral cervical vagotomy (VGX) had less neuroinflammation compared to the shams after laparotomy (LP) at an early stage. To further investigate the roles of mast cells and glutamate in the process, we employed KitW-sh mice and primary bone marrow-derived MCs to verify the glutamate-NR2B axis on MCs once again. Results: Our results demonstrated that there were higher levels of glutamate and BMCs activation as early as 4 h after LP. Meanwhile, vagotomy could partially block the increases and reduce neuroinflammation caused by peripheral inflammation during the acute phase. Excitingly, inhibition of NR2B receptor and knockout of mast cells can attenuateneuroinflammation induced by glutamate. Conclusion: Taken together, our findings indicate that the vagus is a high-speed pathway in the transmission of peripheral inflammation to the CNS. Activation of BMCs triggered a neuroinflammatory cascade. Inhibition of NR2B receptor on BMCs can reduce glutamate-induced BMCs activation, neuroinflammation, and memory impairment, suggesting a novel treatment strategy for POCD.